Reduced Non-Local Integrable NLS Hierarchies by Pairs of Local and Non-Local Constraints - Ma, Wen-Xiu (International journal of applied and computational mathematics, 2022)
We conduct three pairs of local and non-local group constraints for the Ablowitz-Kaup-Newell-Segur matrix eigenvalue problems and generate three reduced non-local integrable nonlinear Schrödinger (NLS) hierarchies. All resulting non-local equations possess infinitely many Lie-Bäcklund symmetries and conservation laws expressed in terms of differential functions of potentials.